COVID‐19 and implications for dermatological and allergological diseases. (27th July 2020) - Buhl, Timo; Beissert, Stefan; Gaffal, Evelyn; Goebeler, Matthias; Hertl, Michael; Mauch, Cornelia; Reich, Kristian; Schmidt, Enno; Schön, Michael P.; Sticherling, Michael; Sunderkötter, Cord; Traidl‐Hoffmann, Claudia; et al.
Summary: COVID‐19, caused by the coronavirus SARS‐CoV‐2, has become pandemic. A further level of complexity opens up as soon as we look at diseases whose pathogenesis and therapy involve different immunological signaling pathways, which are potentially affected by COVID‐19. Medical treatments must often be reassessed and questioned in connection with this infection. This article summarizes the current knowledge of COVID‐19 in the light of major dermatological and allergological diseases. It identifies medical areas lacking sufficient data and draws conclusions for the management of our patients during the pandemic. We focus on common chronic inflammatory skin diseases with complex immunological pathogenesis: psoriasis, eczema including atopic dermatitis, type I allergies, autoimmune blistering and inflammatory connective tissue diseases, vasculitis, and skin cancers. Since several other inflammatory skin diseases display related or comparable immunological reactions, clustering of the various inflammatory dermatoses into different disease patterns may help with therapeutic decisions. Thus, following these patterns of skin inflammation, our review may supply treatment recommendations and thoughtful considerations for disease management even beyond the most frequent diseases discussed here.